Visualization of competitive market structure by means of choice data - Werner Kunz (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2007)
This paper presents a method for visualizing competitive market structures based on scanner panel date where asymmetries are taken into account. For this, I combined consumer choice models based on mixed logit models with three-mode principal component analysis. This approach can be used to unfold a competitive market structure map. The methodology presented is able to quantify the clout and receptivity of various brands. The results can then be visualized over time. Using this approach, guidelines for promotional activities of new brands can be provided, and possible threats from the competition detected.
Keywords: D49; 330; Three-mode PCA; elasticities; joint plots; market structure analysis; Marktforschung; Deskriptive Statistik; Konsumentenverhalten; Logit-Modell; Markenartikel; Marktstruktur